2009
DOI: 10.1007/s00192-009-1010-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of urethral hypermobility and intrinsic sphincteric deficiency on the outcome of transobturator tape procedure: a prospective study with 2-year follow-up

Abstract: A lack of urethral hypermobility may be a risk factor for TOT failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 18 publications
1
27
1
3
Order By: Relevance
“…This type of analysis seeks to circumvent selection bias, as analyzing urethral mobility or VLPP singly. A contemporary Turkish study had a similar conclusion (21).…”
Section: Discussionmentioning
confidence: 57%
“…This type of analysis seeks to circumvent selection bias, as analyzing urethral mobility or VLPP singly. A contemporary Turkish study had a similar conclusion (21).…”
Section: Discussionmentioning
confidence: 57%
“…The underlying pathology has been postulated to involve urethral hypermobility [5], intrinsic urethral sphincter deficiency [5] or any disturbance within the sphincter mechanism [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The type of urinary incontinence determines choice of surgical treatment, to prevent UH by repositioning the urethra into the pelvis to equalize pressure trans mission between the bladder and urethra, and for women with low urethral resistance in ISD to increase the urethral closure pressures. Studies investigating the effects of UH and ISD on the outcome of the commonly performed procedures, such as transobturator tape (TOT) used to treat UH reported that the lack of UH as a contributing factor to SUI may be a risk factor for TOT failure [4] . Also, Sand et al [5] studied women who failed retropubic suspension and found a higher failure rate in those with ISD.…”
Section: Introductionmentioning
confidence: 99%